Experimental Study of Rheological Properties and Oil Displacement Efficiency in Oilfields for a Synthetic Hydrophobically Modified Polymer - Pengcheng Liu (Nature Portfolio, 2017)
Abstract In a previous study, we developed a synthetic hydrophobically modified hydroxyethyl cellulose (HEC) using bromododecane (BD), which we denote as BD-HMHEC. In this work, we continually investigate the rheological properties and its oil displacement efficiency in PuTao well area in Daqing oilfields, China. Results show that BD-HMHEC solution has good viscosification, thermal-resistance, salt-tolerance, shear resistance, and acid/alkali resistance. The storage modulus (G’) and the loose modulus (G”) of the BD-HMHEC solutions increase significantly with increasing BD-HMHEC concentration, and the solution becomes viscoelastic at a sufficiently high BD-HMHEC concentration. The core flooding results showed BD-HMHEC flooding improves oil recovery by 7–14% in comparison with HEC flooding at concentrations of 4,000 mg/L under equivalent conditions. Moreover, BD-HMHEC flooding improves oil recovery by 7–8% after conducting water and hydrolyzed polyacrylamide (HPAM) flooding. The oil displacement mechanism of BD-HMHEC solutions is discussed based on a visual evaluation. The results indicate that BD-HMHEC flooding is a feasible means for improving oil recovery after water/HPAM flooding.